2014
DOI: 10.1016/j.brat.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for insomnia in combat-exposed OEF/OIF/OND Military Veterans: Preliminary randomized controlled trial

Abstract: Objective Chronic insomnia is highly prevalent among military personnel returning from Iraq and Afghanistan. We evaluated the effects of a military version of a brief behavioral treatment of insomnia (BBTI-MV) compared to an information only control (IC) condition in combat-exposed Veterans of Operations Enduring/Iraqi Freedom or Operation New Dawn (OEF/OIF/OND) on insomnia, sleep quality, and daytime symptoms of anxiety and depression. Method Forty OEF/OIF/OND Veterans (Mean age = 38.4 years old, s.d. = 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 77 publications
4
58
1
Order By: Relevance
“…Consistent with previous JITAI studies [18,[32][33][34][35], we found that the implementation of personalized and time-varying JITAI approach improved the outcome of traditional evidence-based treatment. In the current study, we found that the iREST intervention was associated with slightly higher rates-although not statistically significant-of response and remission compared to our previous traditional behavioral approach [16]. Significant improvements in sleep quality and decrease in daytime sleepiness after treatment was observed.…”
Section: Principal Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…Consistent with previous JITAI studies [18,[32][33][34][35], we found that the implementation of personalized and time-varying JITAI approach improved the outcome of traditional evidence-based treatment. In the current study, we found that the iREST intervention was associated with slightly higher rates-although not statistically significant-of response and remission compared to our previous traditional behavioral approach [16]. Significant improvements in sleep quality and decrease in daytime sleepiness after treatment was observed.…”
Section: Principal Resultssupporting
confidence: 51%
“…There were no statistically significant demographic differences between participants in the current study (iREST) and the traditional BBTI study [16] that was used as a control. …”
Section: Demographicsmentioning
confidence: 97%
See 2 more Smart Citations
“…19 In a second study of veterans, mere provision of information regarding sleep was beneficial, although, brief behavioral therapy was superior. 20 The results echo the call for a step-wise approach to insomnia from a British study in which a single session of cognitive behavioral therapy was sufficiently efficacious for a sizable proportion of those with acute insomnia. 21 Amidst the nation's ongoing epidemic of prescription drug abuse, notably, a study of 311,400 veterans from Iraq and Afghanistan demonstrated that 8.4% used more than five drugs that act on the central nervous system, and this polypharmacy was associated with overdosage and suicide-related behaviors.…”
mentioning
confidence: 61%